An 8-Year Breeding Program for Asian Seabass Lates calcarifer: Genetic Evaluation, Experiences, and Challenges - Khang, Pham Van; Phuong, Truong Ha; Dat, Nguyen Khac; Knibb, Wayne; Nguyen, Nguyen Hong (Frontiers in Genetics, 2018)
Selective breeding for marine finfish is challenging due to difficulties in reproduction, larval rearing and on-growth in captive environments. The farming of Asian seabass (Lates calcarifer) has all these problems and our knowledge of the quantitative genetic information (heritability and correlations) of traits necessary for commercial exploitation is poor. The present study was conducted to address this knowledge gap and to provide information that can be applied to sea bass and other aquaculture species. We carried out a comprehensive genetic evaluation for three traits (body weight, total length and survival) collected from a breeding population for Asian seabass over an eight-year period from 2010 to 2017. Statistical analysis was carried out on 4567 adult fish at 105, 180, 270, 360, 450 and 570 days post-hatch (dph). The heritabilities (h2) estimated for body weight and length using linear mixed model were moderate to high (0.12 to 0.78 and 0.41 to 0.85, respectively) and they differed between the measurement periods. Survival during grow-out phase was analysed using threshold logistic and probit models. The heritability estimates for survival rate on the underlying liability scale ( ) varied from 0.05 to 0.21. When they were back-transformed to the observed scale (0/1), the estimates were similar but not significant. In addition, we examined effects of genotype by environment (G×E) interaction on body traits. The genetic correlation for body weight between tank and sea cage cultures were high (0.91-0.94) in the first and second rearing periods (180 and 270dph) but the correlation was decreased to 0.59±0.33 at 360dph. This suggests that the genotype by environment interaction is important for body traits in this population. Furthermore, the genetic correlations of body weights between different measurement periods were moderate and positive. This suggests that body weights measured at different time points may be different traits and selection for improved early weight may not capture all genetic expressions in subsequent rearing periods in Asian seabass. Selection of the nucleus in sea cages may produce genotypes that do not perform equally well in tanks, although this deserves further studies to determine a suitable selection environment and optimise the breeding program.